Using sustainable development tools for solving property rights in Montenegro - Janjusevic, Jelena (Applied Studies in Agribusiness and Commerce, 2013)
In recent months Montenegro has been faced with serious budget problems , one proposed solution of which has been to reduce the number of employees in state administration. Additionally, the costs of living are above the disposable budget of most households, in particular the high cost of electricity. While the government warns about a lack of electricity, the citizens are hardly in the position to cover these costs. Montenegro is dealing with the double challenge of inefficient use of space (the country features over 100,000 illegal homes)(I don’t understand the link between inefficient use of space and illegal homes) and inefficient energy use (Montenegro needs an average of 8.5 times more energy per unit produced than an average EU country). How can these problems be solved in a way which pleases both sides? In this paper, an approach is presented which links the solving of the problem of illegal construction with increasing the level of energy efficiency in households, businesses and other facilities. There is a model developed by UNDP Montenegro – an integrated policy solution to the double challenge of providing energy efficiency measures to incentivise households to legalise their homes. The legalisation of illegal buildings by the introduction of mandatory energy efficiency measures in them may at the same time result in an increase of revenue to the central and local budgets, the reduction of negative impacts on the environment, an increase in employment, the engagement of the economy, a reduction of electricity consumption and thereby to reduce the need to import electricity, and ultimately the increased welfare of the population.